IoT and 5G Networks: A Discussion of SDN, NFV and Information Security - Coêlho, Roger William; Silva, Ronan Assumpção; Martimiano, Luciana Andréia Fondazzi; Leonardo, Elvio João (Journal of the Brazilian Computer Society, 2024)
Having an infrastructure capable of exchanging data at high speed is an efficient way to drive the evolution and development of new applications and existing services. The 5G technology has emerged as a trusted source to meet the increased demand of Internet of Things (IoT) devices connected to the network, in addition to enabling Internet connectivity at high broadband speeds. Another important feature of 5G is to allow the use of Software Defined Network (SDN) and Network Function Virtualization (NFV), mechanisms responsible for performing network configurations through software, as well as the control and management of devices using the configuration network functions or device virtualization. The concern with information security in the 5G network is increasing, as cybercriminals try to access important data that is transported over the network, since the demand for connected IoT devices will be greater, allowing for several possibilities of attacks. The understanding of possible threats and attacks is necessary, so that new measures are taken against cybercrimes presented in the 5G and IoT networks. This paper aims to elucidate some conceptions of what 5G technology is and the use of IoT in this network, contextualizing the SDN and NFV paradigms to allow the configuration of the functionality and management of the network by software. In addition, concerns are reported about possible information security attacks that can occur in 5G networks.